Programa de mentoría en el desarrollo socioemocional de los estudiantes del nivel secundaria en Jenaro Herrera 2025 - Zevallos del Aguila, Cheryl Flavio (2025)
The goal was to verify the extent to which the mentoring program enhances the social-emotional growth of secondary school students at Jenaro Herrera 2025. The research was conducted quantitatively and evaluatively, taking into account the time frame and performing the corresponding controls: Therefore, the design is quasi-experimental because the program focused on mentoring. It was modified to observe its impact on socio-emotional development through pre- and post-tests. The total population was 474, and the sample consisted of 41 students.The descriptive study presents socio-emotional development before and after mentoring. It is noted that 37 (90.2%) gave a low response, 2 (4.9%) gave a medium response, and 2 (4.9%) gave a high response. After the intervention, 1 (2.4%) gave a low rating (37, 90.2%), while 3 (7.3%) rated it as high. In the inferential analysis, the two-tailed significance values of socio emotional development before and after the mentoring program were determined. It was found that the value is less than 0.05, which implies that these distributions do not conform to a normal distribution. Thus, for the hypothesis test for paired or related samples, the Wilcoxon signed-rank test was chosen to test the study hypothesis: The mentoring program significantly enhances the socio-emotional growth of secondary school students at Jenaro Herrera 2025. A significance level ∞ = Alpha = 0.05 = 5% is reached. The test statistic is standardized Z to compare linked or paired samples, in our case, the observation of socio-emotional progress. Therefore, an error of 0.000% is decided upon, concluding with 95% confidence the study hypothesis: The mentoring program significantly enhances the social-emotional growth of secondary school students at Jenaro Herrera 2025.